Determinants of voluntary non-financial disclosures in annual reports of listed companies in Singapore. - Chew, Julia Alexis Li Lian. (2008)
This study identifies and examines the firm-specific determinants drawn from agency theory that influence the voluntary disclosure of non-financial information by Singapore listed companies. This study finds that technology, growth opportunities, size, auditor, number of non-executive directors and leverage help explain variations in voluntary disclosure of non-financial information. High technology companies disclose more non-financial information, but only up to a certain point, as perhaps further disclosure might put them at a competitive disadvantage. The association between growth opportunities and non-financial disclosure was in the opposite direction to that predicted.